JFK’s Forgotten Crisis: Tibet, the CIA, and Sino-Indian War - Ms. Fatima Ilyas (CISS Insight Journal, 2015)
JFK’s Forgotten Crisis: Tibet, The CIA, And Sino-Indian War by Bruce Riedel is a comprehensive piece of history which provides perspective on the 1962 Sino-Indian war and the crisis it had unleashed. Bruce Riedel is a 30-year veteran of the CIA, and has served as an adviser to four US presidents on US foreign policy, including President Barack Obama. Riedel is an outstanding scholar of both the Middle East and South Asia. He puts Sino-Indian war back in focus which had been overshadowed by Cuban Missile Crisis. Along with that, the book explores the forgotten role of CIA in Tibet. In October 1962, Kennedy had to deal with both the Cuban Missile Crisis and a war between China and India. After almost half century, the Sino-Indian crisis has developed its own legacy including the border dispute and growing arms race. Bruce Riedel argues that Sino-Indian war had as much impact on US policy as the Cuban Crisis. JFK’s administration is mostly remembered with reference to the Cuban Missile Crisis. Times were tougher for JFK when he took over as president because of the Bay of Pigs disaster in Cuba, which took place soon after he took office. It was inarguably a huge success, when he was able to force removal of Soviet nuclear missiles from Cuba. Meanwhile, the South Asian pot was still boiling. The iconic success in Cuba has screened from the public eye the fact that JFK also had a deep interest in South Asia particularly India, in the context of China as a growing power.